Urgensi Mengawal Kebijakan Hukum Di Indonesia Pada Masa Darurat Kesehatan Pandemi Covid-19 - Fakhriah, Syahriati (Jurnal Kepastian Hukum dan Keadilan, 2021)
The increasingly widespread spread of the Covid-19 pandemic has caused a national and even global health crisis. The Indonesian government has declared a health emergency status on March 31, 2020 through Presidential Decree No. 11 of 2020 concerning the Determination of a Covid-19 Public Health Emergency. However, this kind of emergency crisis cannot be taken lightly. Because an emergency situation (state of emergency) gives extraordinary powers to the state that are not possessed during normal situations, this is commonly referred to as Emergency Power. The type of research used to answer the problem is normative legal research. If this policy is indeed the chosen middle way for the government to restore the economy, protection for the people still needs to be prioritized. One form of protection is the existence of legal instruments issued as a guarantee of protection for the people. It is things like this that should be used as a concern for the DPR to carry out its functions as mentioned above. Even so, everyone's awareness to stop the spread of Covid-19 is no less important to emphasize to all people. Education related to Covid-19 needs to be conveyed to all circles of society, so that awareness is planted to stop the spread of Covid-19. Balanced cooperation between the people and the government is very much needed in these conditions, because the government will not be able to reach the optimal point without the participation of the community.Keywords: Government, Power, Covid-19, Society.